Anna Mobile Digitalization System Design for Outpatient Registration Services - Hasinuddin, M.; Isnaini, Alvin; Kulsum, Ummi (GLOBAL HEALTH SCIENCE GROUP, 2024)
The use of online registration for outpatient services at the Hospital provides flexibility and ease of access for patients. This will increase patient satisfaction with Hospital services. The purpose of this innovation project is to produce an effective and innovative ANNA Mobile design framework in an effort to create convenience in outpatient registration services at RSU ANNA Medika Madura. Methods: This innovation project uses the type of Research Development with a Formative research design using the ADDIE development model. The subject of research in this innovation project is the digitalization of outpatient registration at RSU ANNA Medika Madura. The development was carried out by involving several complaints and customers (patients) in the feasibility test of the development product, namely the ANNA Mobile Design Framework. Results: The results of this innovation project are in the form of an ANNA Mobile design framework which is considered feasible and can be implemented into an effective and innovative ANNA Mobile application in an effort to create convenience in outpatient registration services at RSU ANNA Medika Madura. Conclusions: An effective and innovative ANNA Mobile design in an effort to create convenience in outpatient registration services at RSU ANNA Medika Madura.